A Fast and Robust Approach for the Green Synthesis of Spherical Magnetite (Fe3O4) Nanoparticles by Tilia tomentosa (Ihlamur) Leaves and its Antibacterial Studies - Shashanka Rajendrachari; Abdullah Cahit Karaoglanli; Yusuf Ceylan; Orhan Uzun (Tabriz University of Medical Sciences, 2020)
Background: In the past few years, Magnetite (Fe3O4) nanoparticles have gained a significant research interest in the field of biology, chemistry, metallurgy due to their wide range of applications. Some of their important applications include drug delivery, chemotherapy, low-friction seals, magnetic fluid, adsorbent, recovery of hazardous wastes, etc. Methods: In the present paper, we reported an eco-friendly route of preparing magnetite nanoparticles by using leaves of Tilia Tomentosa (Ihlamur) followed by calcination at 400 ˚C for 15 minutes. Results: The bandgap energy of the prepared Fe3O4 nanoparticles was studied by UV-Visible spectroscopy and the value was found to be 3.31 eV. The scanning electron microscopy (SEM) image showed the spherical magnetite nanoparticles with an average size of 25 nm. The phases and thermal properties of Fe3O4 nanoparticles were studied by using X-ray diffraction, thermogravimetric (TG) and differential thermal analysis (DTA). The enthalpy change of Fe3O4 nanoparticles was calculated by using the DTA curve and the value was found to be 4.97 kJ/mol at 8˚C/min heating rate. The antimicrobial activity of Fe3O4 nanoparticles was carried out by the minimum inhibition concentration (MIC) assay method. Except for B. subtilis, Fe3O4 nanoparticles demonstrated significant antibacterial property.Conclusion: The prepared magnetite nanoparticles showed excellent thermal stability and less weight loss over a 30-1000 ˚C temperature range. The size of the prepared magnetite nanoparticles is very less therefore they interacted effectively with the organelle, enzymes, and cells of bacteria and inhibited bacterial growth by killing them.